2018
DOI: 10.1096/fj.201801319r
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular metalloprotease activity controls intraneuronal Aβ aggregation and limits secretion of Aβviaexosomes

Abstract: Accumulating evidence suggests that the abnormal aggregation of amyloid‐β (Aβ) peptide in Alzheimer's disease (AD) begins intraneuronally, within vesicles of the endosomal‐lysosomal pathway where Aβ is both generated and degraded. Metalloproteases, including endothelin‐converting enzyme (ECE)‐1 and ‐2, reside within these vesicles and normally limit the accumulation of intraneuronally produced Aβ. In this study, we determined whether disruption of Aβ catabolism could trigger Aβ aggregation within neurons and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…The level of Aβ42 was below the assay detection level (data not shown). The reduction in Aβ level could be due to the activity of EV‐associated Aβ‐degrading enzymes such as neprilysin, 47 insulin‐degrading enzyme (IDE), 48 or endothelin‐converting enzymes‐1 and −2 (ECE‐1 and ECE‐2), 49 suggested to be active in the extracellular space 50 . Thus, we pretreated the brain EVs with the metalloprotease inhibitors phosphoramidon and thiorphan, in order to inhibit the activities of these enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…The level of Aβ42 was below the assay detection level (data not shown). The reduction in Aβ level could be due to the activity of EV‐associated Aβ‐degrading enzymes such as neprilysin, 47 insulin‐degrading enzyme (IDE), 48 or endothelin‐converting enzymes‐1 and −2 (ECE‐1 and ECE‐2), 49 suggested to be active in the extracellular space 50 . Thus, we pretreated the brain EVs with the metalloprotease inhibitors phosphoramidon and thiorphan, in order to inhibit the activities of these enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, treatment of BV‐2 cells with statins enhanced exosome secretion carrying IDE, contributing to Aβ clearance, although the underlying mechanisms remain unclear (Tamboli et al., 2010). Endothelin‐converting enzymes 1/2 and metalloproteinases, are also capable of degrading Aβ, and are likewise found into exosomes (Pacheco‐Quinto et al., 2018).…”
Section: Exosomes Protective Role and Therapeutic Potential In Admentioning
confidence: 99%
“…Aβ and exosomes were also found to co-localize inside neurons, thus suggesting that exosomes participate in Aβ sorting and oligomerization. 65 Tau is a core protein associated with the pathogenesis of AD and is secreted in exosomes. 66 Our previous study showed that the up-regulation of mTOR facilitates the release of tau into the extracellular space in an exosome-independent fashion in SH-SY5Y cells.…”
Section: The Role Of Exosomes In Ad the Pathogenic Role Of Exosomes Imentioning
confidence: 99%